Investor Sentiment and IPO Pricing: An Empirical Analysis of the Quotations from Institutional Investors in Chinese A-shares Market - LI, HENAN (2018)
This study investigates the Initial Public Offering (IPO) pricing adjustment process on Chinese A-share market, over a particular sample period from 1st November 2010 to 31st December 2017. From October 2010, the China Securities Regulatory Commission (CSRC) required that institutional investors should disclose the inquiry information. This therefore introduces investor sentiment indicators into the process of IPO pricing adjustments. In comparison to previous studies about IPO under-pricing, this study applies the IPO pricing adjustment analysis, to investigate the influence of investor sentiment and underwriter behaviours. The results of this study suggest that the underwriter asymmetric theory, exists in China, with positive investor sentiment increasing the quotation of institutional investors. Therefore, investor sentiment can be seen to provide a reasonable explanation for the high under-pricing rate. Additionally, under the book building, pricing mechanism, the analysis of IPO pricing process’ need to consider the underwriters personal motivations of pricing, in the final pricing stages. Under this market-focused pricing mechanism, regulators may try to utilise the limitations of an underwriter’s reputation, to regulate a pricing issue.